ANALISIS EMBOLI PARU MENGGUNAKAN DUAL ENERGY LUNG PERFUSION BLOOD VOLUME CT ANGIOGRAFI PULMONAL PADA PESAWAT DUAL SOURCE CT SCAN - Himmatus Suroyya, Sherin; Nurcahyo, Kukuh; Winarno, Guntur; Gunawati , Shinta (Perhimpunan Radiografer Indonesia (PARI), 2021)
Background: DECT-based scanning protocol with dual source CT scan, recommended for pulmonary perfusion, the protocol aims to evaluate pulmonary artery and pulmonary perfusion from CT contrast examination. Purpose: The purpose of this research was to determine how the pulmonary angiography CT scan technique to analyze pulmonary embolism using Dual Energy Lung Perfusion Blood Volume on Dual Source CT Scan. Methods : This research is a qualitative descriptive with primary data sources, namely CT Scan of Pulmonary Angiography patients with a Pulmonary Embolism Suspect using 128 slice Dual Source Dual Energy Siemens Somatom CT Scan analyzed using PBV Dual Energy Lung using the Region Of Interest (ROI) analysis technique and using material decomposition parameters, from July to October 2020 at National Central General Dr. Cipto Mangunkusumo Jakarta Hospital. Results: The results obtained were the process from the beginning of the patient registration, which was carried out by CT Pulmonary Angiography examination in the administration until the examination was completed. The CT scan technique for pulmonary angiography was conducted using 128 slice Dual Source Dual Energy Siemens Somatom CT Scan to analyze pulmonary embolism using the post processing Lung Perusion Blood Volume application. Conclusion : The results of the examination of the patient showed a picture of pulmonary embolism in the superior and inferior branches of the right pulmonary artery, and still visible contrast flow to the distal branch.